Using Literature Circles strategy in Teaching Reading Comprehension - Neng Fitri Ananda Julianti (Universitas Majalengka, 2018)
This research is conducted in order to improve students' Reading Comprehension of Narrative Text by Using Literature Circles Strategy at the first grade of senior high school in Majalengka. This research used a Classroom Action Research (CAR) which is conducted to solve the students' problem in English reading. The Classroom Action Research (CAR). The researcher did two cycles in which each cycle consist of planning, acting, observing, and reflecting. The data were gathered through qualitative and quantitative data. The qualitative gained by analysing the observation and interview. Then quantitative data were obtained from the students' test score of cycle I and cycle II. The finding of this research indicated that the implementation of literature circles strategy was success full since there is an improvement in students' reading comprehension in narrative text. The finding showed an improvement in students' reading comprehension of narrative text from the average of reading test narrative text in cycle 1 was 78, 61 to 89, 44 the average of reading comprehension in cycle 2. Based on the finding mentioned before, the researcher suggests that English teacher could implement using literature circles strategy in teaching reading narrative text in order to motivate students in learning English reading in narrative text.Keywords: Reading Comprehension, Narrative text, Literature Circles Strategy